1993
DOI: 10.1007/bf00008375
|View full text |Cite
|
Sign up to set email alerts
|

Rice field ecology and fish culture — an overview

Abstract: Rice fields are an integral part of the landscape throughout most of the tropics. Rice is also grown widely in higher latitudes. Most rice cultivation is done in flooded fields where a temporary aquatic fauna is generated. Rice cultivation has sustained some of the oldest civilizations but the use of the aquatic phase for raising a crop of fish has not been practiced widely although fragmentary records indicate that rice and fish have been cultivated concurrently but rarely over 2 or 3 millennia. We have more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 29 publications
0
76
0
1
Order By: Relevance
“…Several reviews on historical, socio-economic, and ecological aspects of rice-fish fanning have been published in the past decade with either a global or a national focus (Li 1988;Fernando 1993a;Halwart 1994;MacKay 1995;Choudhury 1995;Little et al 1996).…”
Section: Omentioning
confidence: 99%
“…Several reviews on historical, socio-economic, and ecological aspects of rice-fish fanning have been published in the past decade with either a global or a national focus (Li 1988;Fernando 1993a;Halwart 1994;MacKay 1995;Choudhury 1995;Little et al 1996).…”
Section: Omentioning
confidence: 99%
“…Moreover, Bacillariophyceae prefer to exhibit periphytic life on organic substrates over planktonic life [30].Morphological and physiological nature of rice stem might have also influenced the development of attached algae, as the submerged rice had the ability to secrete mucilage to form stalks or mucilaginous matrices, allowing attachment to substrates [31]. Seasonal changes of periphyton in natural system are affected by seasonal changes in the vegetation upon which it grows [32]. Rice vegetation is a rapidly changing system [33]and therefore the rice stem greatly influences succession pattern of periphyton on it.…”
Section: IVmentioning
confidence: 99%
“…It harbours lots of phytoplankton and filamentous higher algae in its aquatic phase [64]. All these aquatic fauna and flora play important role on the overall ecology of rice field.…”
Section: Periphyton In Waterlogged Rice Fieldsmentioning
confidence: 99%
“…Horne and Golderman [34] also suggested that seasonal changes of epiphyton in natural system are affected by seasonal changes in the vegetation upon which it grows. If such considerations are hypothesized, the rice vegetation is rapidly changing system [64] and therefore the rice stem greatly influences succession pattern of periphyton on it. Most of the attached forms including diatom were secured to living substrate by jelly-like secretions, while others were attached to gelatinous stalks [84].…”
Section: Self-substrating To Rice-fish Culturementioning
confidence: 99%